EFEKTIVITAS EFEKTIVITAS PENGGUNAAN SUMBER BELAJAR BERBASIS ONLINE DALAM MENINGKATKAN PRESTASI BELAJAR PAI SISWA KELAS VII DI SMPIT TUNAS HARAPAN ILAHI KOTA TANGERANG: EFEKTIVITAS PENGGUNAAN SUMBER BELAJAR BERBASIS ONLINE DALAM MENINGKATKAN PRESTASI BELAJAR PAI SISWA KELAS VII DI SMPIT TUNAS HARAPAN ILAHI KOTA TANGERANG - abdul basyit; R Tommy Gumelar (ISLAMIKA, 2023)
ABSTRACT This study aims to determine the quality of student achievement in PAI subjects. And to find out whether there is effectiveness between online learning resources on PAI learning achievement for class VII students at SMPIT Tunas Harapan Divine, Tangerang City. The results of this study concluded that there was a negative and significant influence between digital literacy (X) on the learning achievement of PAI (Y) class VII students at SMPIT Tunas Harapan Divine, Tangerang City. The contribution of digital literacy to PAI learning outcomes is 10.8% and 89.2% is influenced by other factors. Keywords: Online Learning Resources Learning Achievement, PAI